Functional and cost- benefits of geosynthetics as subgrade reinforcement in the design of flexible pavement - Sivapriya, S. Vijayasimhan; Ganesh-Kumar, Shanmugam (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The vertical stress exerted by the vehicles will be high in a populated road and to increase the bearing capacity of subgrade characteristics, geosynthetic material can be used. In the current study different geosynthetic material such as geo-grid, geo-textile and geo-membrane were used to as a subgrade reinforcement member inside the CBR mould for understanding the improvement in subgrade  for single, two and three geosynthetic layering  in the CBR mould. The results show there was a constant increase in the bearing with the increase in a number of layers and this improvement varied with type of geosynthetic materials also. Among three geosynhteic materials, geogrid shows improved CBR characteristics. Finally, Cost analysis and design of flexible pavement were carried for an optimum number of layers for geogrids. There was reduction of about 6.38% in the cost of construction when using geogrid as subgrade reinforcement member.